2011
DOI: 10.1007/s10518-011-9274-2
|View full text |Cite
|
Sign up to set email alerts
|

Proposal for a soil classification based on parameters alternative or complementary to Vs,30

Abstract: The selection of specific elastic response spectra according to soil categories is the easiest way to account for site effects in engineering projects and general-purpose hazard maps. Most of the international seismic codes make use of the average shear wave velocity of the upper 30 m (Vs ,30 ) to discriminate soil categories, although some doubts arose about the capability of Vs ,30 to predict actual soil amplification. In this work we propose two soil classifications in which the soil fundamental frequency (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
62
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 118 publications
(65 citation statements)
references
References 24 publications
2
62
0
1
Order By: Relevance
“…Gallipoli et al, 2004;Gosar, 2012). Secondly, it can be a complement to the average S-wave velocity in the upper 30 m (V s,30 ) as proposed by Ansal (2004) and Luzi et al (2011). Most of the seismic codes make use of the V s,30 to discriminate soil categories, although some doubts exist about the capability of V s,30 to predict the actual amplification of sediments.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Gallipoli et al, 2004;Gosar, 2012). Secondly, it can be a complement to the average S-wave velocity in the upper 30 m (V s,30 ) as proposed by Ansal (2004) and Luzi et al (2011). Most of the seismic codes make use of the V s,30 to discriminate soil categories, although some doubts exist about the capability of V s,30 to predict the actual amplification of sediments.…”
Section: Discussionmentioning
confidence: 99%
“…Most of the seismic codes make use of the V s,30 to discriminate soil categories, although some doubts exist about the capability of V s,30 to predict the actual amplification of sediments. Luzi et al (2011) showed that the standard deviation associated with ground motion prediction is significantly reduced when the classification is based on the couple of variables V s,30 -f 0 . Finally, the resonance frequency is useful in calibrating the V s profile, which can be uncertain even when the microtremor array or the MASW measurements are conducted.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For examples, sites are classified into six categories in US [1] mainly from average shear wave velocity Vs30,and are classified into four categories in China from Vs20 and overburden thickness [2]. Site predominate period Tp is suggested to be taken into account in site classification in these years [3], basically from microtremor studies [4], [5]. A way to do this from Vs30is presented in this paper.…”
Section: Introductionmentioning
confidence: 99%